Syntesis of Glutardehide Crosslinked Superporous Chitosan with Polyphynil Alcohol Addition for Peat Water Humic Acid Absorption - Dahlena Ariyani; Uripto T Santoso; Radna Nurmasari; Utami Irawati; Iriansyah Iriansyah (Center for Journal Management and Publication, 2015)
This research aims to synthezise the superporous adsorbent from chitosan using glutaraldehyde as a cross linker, NaHCO3 as a porogen, and polyvinyl alcohol (PVA) as a reinforcing agent. Generally, the reaction of adsorbent synthesis was carried out through four steps: (1) the addition of PVA to the chitosan solution, (2) the addition of porogen, (3) the crosslinking of chitosan, and (4) the releasing of porogen. The obtained adsorbents were characterized by Fourier Transform Infra Red (FTIR) Spectroscopy, photograph of Digital Microscope (DM), and Scanning Electron Microscopy (SEM) to measure the porosity. The adsorbent was then be applied to adsorb of HA for adsorption capacity determination. The results showed that the addition of PVA and porogen during adsorbent synthesis has produced adsorbent with more compact and flexible physical properties and greater porosity. The adsorption test showed that the adsorption capacity of KPG is 33.07 mg/g. However, if the amount of used adsorbent is larger (based on the chitosan mass 1 g), the capacity adsorption of KPG is 141.74 mg/g. The initial concentration of HA contained in peat water was 45.64 mg/L, KPG can adsorb of HA as much as 95%.